Bilateral Bisphosphonate-related Atypical Femoral Neck Fracture in a Patient with Familial Mediterranean Fever: A Case Report - Sibel Balıkçı; Bilinç Doğruöz Karatekin (Türk Osteoporoz Dergisi, 2022)

(untitled)
The authors present a rare case of bilateral bisphosphonate-related femoral neck fracture in a patient with Familial Mediterranean fever. Chronic subclinical inflammation that continues in the attack-free period is thought to cause osteopenia/osteoporosis. Locomotor system symptoms are frequently observed during the clinical course of the disease, and in the presence of hip pain in these patients, atypical femur fractures should be considered in addition to the hip involvement of the disease. Although bisphosphonate-related atypical femoral fractures are mostly seen in the diaphysis, atypical femoral neck fractures have also been defined recently, as in this case.